PENGEMBANGAN MEDIA DAKOTA PADA MATERI KPK KELAS IV SD NEGERI 101772 TANJUNG SELAMAT - Nanda Faradina; Sujarwo sujarwo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This development research aims to develop Dakota media on KPK material that is suitable for use in the learning process. This research is a type of research and development using the 4D development procedure developed by Thiagarajan. In this research, the researcher carried out the 4D development procedure only up to stage 3, namely define, because the focus of this research was only to develop Dakota media on KPK material that was suitable for use in the learning process. The instrument used to collect data is a questionnaire given to validators, namely media expert validators, material expert validators and learning expert validators. Based on the validation results from the media expert validator, a score of 92 was obtained. From the material expert validation results, a score of 97 was obtained, and from the Teacher expert validation results, a score was obtained of 95. The average score obtained from the overall assessment of the three expert validators was 94.6 . Based on the assessment score criteria, it can be said that the Dakota media in the KPK material developed is very valid/very suitable for use in the learning process